Micromobility support in HIP: survey and extension of host identity protocol - Novaczki, S.; Bokor, L.; Imre, S. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
The host identity protocol (HIP) is a rather new concept that separates the identity and location information both represented by IP addresses in the current Internet architecture. HIP also has capabilities and efficient extensions to serve macromobility, but it shows unnecessary signaling overhead and handoff latency, when used in micromobility environments. This paper introduces a new method how HIP can be extended to serve as a micromobility protocol